2011
DOI: 10.1016/j.jplph.2011.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, N2 fixation and taproot reserves during the cutting regrowth cycle of alfalfa under elevated CO2 and temperature

Abstract: Future climatic conditions, including rising atmospheric CO(2) and temperature may increase photosynthesis and, consequently, plant production. A larger knowledge of legume performance under the predicted growth conditions will be crucial for safeguarding crop management and extending the area under cultivation with these plants in the near future. N(2) fixation is a key process conditioning plant responsiveness to varying growth conditions. Moreover, it is likely to increase under future environments, due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 95 publications
4
23
0
3
Order By: Relevance
“…This change is considered a key factor determining plant productivity under limited water supply [35], and it is mentioned as an adaptive response and a strategy to improve crop performance under limited water conditions [14]. In accordance with our results, many studies have found that WUE p increased with increasing water stress in alfalfa plants [36]. This change keeps being controversial, because improving WUE may confl ict with the high growth rate for many species [37].…”
Section: Discussionsupporting
confidence: 85%
“…This change is considered a key factor determining plant productivity under limited water supply [35], and it is mentioned as an adaptive response and a strategy to improve crop performance under limited water conditions [14]. In accordance with our results, many studies have found that WUE p increased with increasing water stress in alfalfa plants [36]. This change keeps being controversial, because improving WUE may confl ict with the high growth rate for many species [37].…”
Section: Discussionsupporting
confidence: 85%
“…Similar results have been reported by Wang et al (2009) who also observed an increase in dry weight of spinach plants when nitrogen: ammonium nitrogen changed from 1:0 to 0:1, while Szalai et al (2010) have also reported an increase of stem dry matter in purslane when ammonium was the sole nitrogen source. Additionally, uncut plants (H3 treatment) had higher dry weight than cut plants in almost every treatment (apart from treatment F4), which could be attributed to the consumption of more carbohydrate reserves for regrowth, comparing to the uncut plants (Erice et al, 2011; Table 2). …”
Section: Resultsmentioning
confidence: 95%
“…Higher leaf dry weights were achieved for the second harvest crop for all cultivars, meaning that differences in plant growth occur between harvests (Figure 1). The higher leaf dry weights for the second harvest crop may have been influenced by the ability of this species to store and utilize carbohydrate reserves in the tap root (Bewley, 2002;Cry et al, 1990;Erice et al, 2011). The perennial nature of the plant indicates that it is adapted to produce new vegetative growth once conditions become favorable.…”
Section: Perennial Wall Rocketmentioning
confidence: 99%